Peran Kepala Sekolah Sebagai Administrator Pendidikan dalam Meningkatkan Mutu Pendidikan Di Sekolah - Sibuea, Rolisa; Prasasti, Riska Dwi (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2022)
The principal plays an important role in the progress of the school, therefore the principal must have good leadership responsibilities to be able to manage teachers, administrative staff and other school staff. In carrying out his duties as a school administration of the school. The principal is in charge of supervising all school staff and employers. A school is very dependent on the skills of its leaders in leading the school. This research is a qualitative research using library research methods derived from documents boos and journals or other literaturethat is used to strengthen the argument that the prinscipal as a school administratoris the main driver in achieving a school"s success. The principal as a school administrator plays a role in school management such as planning, organizing the implementation of supervision, guidance, and school financing. The principal is responsible for the success of the school he leads.